2008
DOI: 10.1016/j.jpain.2008.01.334
|View full text |Cite
|
Sign up to set email alerts
|

Affective Analgesia Following Muscarinic Activation of the Ventral Tegmental Area in Rats

Abstract: Cholinergic stimulation of dopamine neurons in the ventral tegmental area (VTA) underlies activation of the brain reward circuitry. Activation of this circuit is proposed to preferentially suppress the affective reaction to noxious stimulation. Vocalization afterdischarges (VADs) are a validated model of the affective response of rats to noxious tailshock. The antinociceptive action of the acetylcholine agonist carbachol microinjected into the VTA on VAD threshold was compared to its effect on the thresholds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 62 publications
3
10
0
1
Order By: Relevance
“…Consistent with our previous reports (Borszcz, 1993; Harte et al, 2000; Nandigama and Borszcz, 2003; Kender et al, 2008), responses organized rostrally within the neuraxis were rarely generated without those integrated more caudally. VAD generation, without concomitant elicitation of VDS and SMR occurred on 1.14% of all trials.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with our previous reports (Borszcz, 1993; Harte et al, 2000; Nandigama and Borszcz, 2003; Kender et al, 2008), responses organized rostrally within the neuraxis were rarely generated without those integrated more caudally. VAD generation, without concomitant elicitation of VDS and SMR occurred on 1.14% of all trials.…”
Section: Resultssupporting
confidence: 92%
“…Consistent with the affective analgesia hypothesis, we reported that microinjection of carbachol into VTA produced dose-dependent suppression of vocalization discharges (VADs) in rats (Kender et al, 2008). VADs occur immediately following application of noxious tail shock and are a validated rodent model of pain affect (Caroll and Lim, 1960; Borszcz, 1993, 1995, 2006; Borszcz and Spuz, 2009).…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…2629,35,44 The failure to observe an increase in SMR threshold does not reflect the resistance of this response to antinociceptive treatments. In previous studies, administration of morphine into the rostral ventromedial medulla or ventrolateral periaqueductal gray (vlPAG) produced significant increases in SMR, VDS, and VAD thresholds 8,9,11,14 and the intrathecal administration of morphine, serotonin, or norepinephrine was equally effective in raising SMR, VDS, and VAD thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of analogous affective aspects of pain in nonverbal animals has been challenging. Several preclinical approaches have been employed for this purpose, including vocalization after discharge in rats following electrical tail shock 60 and evaluation of facial grimace that detects pain affect of short and intermediate, but not longer, duration 61 . Recently, operant measures have been developed that use pain-motivated behavior to capture affective features of pain in animals.…”
Section: Preclinical Measures Of Pain Affectmentioning
confidence: 99%